2003
DOI: 10.1016/s1053-0770(03)00046-6
|View full text |Cite
|
Sign up to set email alerts
|

Left double-lumen tubes: clinical experience with 1,170 patients

Abstract: M ODERN DISPOSABLE plastic double-lumen tubes (DLTs) are generally safe and easy to use. 1,2 However, a misplaced or improperly used DLT can jeopardize any procedure and even injure the patient. This article reviews considerations for the selection and placement of left-sided DLTs based on data collected from a large series of patients undergoing thoracic procedures requiring one-lung ventilation (OLV) at this institution. Although the information presented represents the authors' experience at a single center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
3
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(111 citation statements)
references
References 98 publications
3
94
3
11
Order By: Relevance
“…The wall of the distal bronchus blocks the DLT tip; we cannot insert it deeply. Both Klein et al 13) and Brodsky et al 14) reported the incidence of displacement with patient repositioning, but neither group calculated the amount of displacement. Although Yoon et al 15) reported the amount of displacement, they determined this under FOB and did not compare the ADP between the supine and lateral positions.…”
Section: Discussionmentioning
confidence: 99%
“…The wall of the distal bronchus blocks the DLT tip; we cannot insert it deeply. Both Klein et al 13) and Brodsky et al 14) reported the incidence of displacement with patient repositioning, but neither group calculated the amount of displacement. Although Yoon et al 15) reported the amount of displacement, they determined this under FOB and did not compare the ADP between the supine and lateral positions.…”
Section: Discussionmentioning
confidence: 99%
“…Elles sont utilisées depuis plus de 50 ans; la plupart des anesthésiologistes et des chirurgiens les connaissent donc bien et savent bien les utiliser. [2][3][4][5][6] La décision d'avoir recours à une sonde endotrachéale double lumière ou un bloqueur bronchique se fonde sur trois facteurs : la sécurité des patients, l'aise de l'anesthésiologiste avec le dispositif choisi, et la préférence du chirurgien. Malheureusement, dans certaines situations, ces trois facteurs sont irréconciliables.…”
Section: Stratégies D'isolationunclassified
“…They have been used for more than 50 years, and as a result, most anesthesiologists and surgeons are familiar with them and are comfortable with their use. [2][3][4][5][6] The decision whether to use a DL-ETT or BB depends on three factors: patient safety, the anesthesiologist's comfort with the selected device, and the surgeon's preference. Unfortunately, there are sometimes situations where these three factors cannot coincide.…”
mentioning
confidence: 99%
“…Rates of hypoxemia as low as 1% have been reported. 9 Nevertheless, hypoxemia likely continues to occur in up to 10% of patients and remains a significant clinical concern. 10 Failure of lung isolation is a well-recognized mechanism for intraoperative hypoxemia.…”
Section: Physiology Of Olvmentioning
confidence: 99%
“…On a rapporté des taux d'hypoxémie aussi bas que 1 %. 9 Ceci étant dit, l'hypoxémie survient probablement encore chez près de 10 % des patients et demeure une inquiétude clinique importante. 10 Une mauvaise isolation du poumon est un mécanisme bien connu provoquant l'hypoxémie peropératoire.…”
Section: Au Début De La Vup Et Au Besoinunclassified